Reduced health-related quality of life in children with achalasia. (29th September 2015) - Marlais, M; Fishman, J; Fell, J; Rawat, D; Haddad, M
Abstract : Background: Achalasia is a rare oesophageal motility disorder which occasionally affects children. The management of achalasia is challenging and affected children often experience significant morbidity even after treatment. Quality of life (QoL) has never been studied in children with achalasia. Aim: The authors assessed self-reported QoL in children with achalasia aged 5–18 and compare this with both disease and healthy control children in a prospective study. Methods: All children diagnosed with achalasia at one hospital were asked to participate in this study by completing the self-report module of the validated PedsQL generic QoL assessment. All children attending a tertiary paediatric gastroenterology clinic from February 2009 to May 2009 with chronic constipation or inflammatory bowel disease were asked to participate in this study as disease controls. The PedsQL considers physical, emotional, social and school domains and is scored from 0–100. Healthy children were also recruited from the same site. Ethical approval was obtained and informed parental consent taken for all children. Groups were compared using the Mann–Whitney U-test. Results: 161 children completed the assessment (90 (56%) male, mean age 11.3 years±3.4) including 17 children with achalasia, 44 with chronic constipation, 59 with inflammatory bowel disease and 41 healthy children. QoL was significantly lower in children with achalasia compared to both children with IBD (73 vs 82, p=0.028) and healthy children (73 vs 84, p=0.002), and was comparable to that of children with chronic constipation (73 vs 74, p=0.88). Conclusion: Children with achalasia report a significantly lower QoL compared to children with inflammatory bowel disease and healthy children. Further research is required to evaluate QoL in relation to therapeutic intervention so that recommendations may be made to improve clinical outcomes.